The half‐life and exposure of cefuroxime varied in newborn infants after a Caesarean section. (27th June 2016) - Zachariassen, G; Hyldig, N; Joergensen, JS; Nielsen, DS; Greisen, G
Abstract: Aim: No information was available on how fast intravenous cefuroxime administered to pregnant women before a Caesarean section was cleared in newborn infants. This study investigated the drug's half‐life and the exposure of healthy newborn infants after their mothers received the drug. Methods: Healthy mothers received a single dose of cefuroxime 15–60 minutes before skin incision. One blood sample was drawn from the umbilical cord, and two blood samples were drawn from the infant after delivery. Total plasma cefuroxime (μg/mL) was measured using high‐pressure liquid chromatography. Results: Cefuroxime was given to 22 mothers, including two who had twins. The concentration of cefuroxime varied significantly among infants (p < 0.001), while the rate of decline did not (p = 0.24). The median cefuroxime half‐life was 3.5 hours (range 2.9–5.5), which was approximately three times longer than in normal adults and seemed to clear within 24 hours. The median area under the concentration–time curve was 65.0 hour μg/mL (range 31.7–162.4). Conclusion: We found that the cefuroxime half‐life after a Caesarean section varied among infants and was longer than in normal adults but cleared within 24 hours. Exposure to cefuroxime in newborn infants may influence the gut microbiota and should be investigated further.